EVALUATION OF INTEGRATED ISLAMIC SCHOOL NETWORK IMPLEMENTATION - Tuti SUGIARTI (Journal of Education and Leadership in Education, 2022)
This research aims to reveal and assess the implementation of the integrated islamic school network curriculum at SDIT Harum, North Jakarta. The approach method used in this study is an evaluative approach, where the researcher intends to collect data on policy implementation. The evaluation model chosen in this study is the Discrepancy Evaluation Model (DEM), by collecting and using observations, structured interviews and documentation. The design of the integrated islamic school network curriculum is a combination of the content of the integrated islamic school network curriculum, the content of the national curriculum and local content. the integrated islamic school network curriculum places more emphasis on internalizing Islamic values in every content of the National curriculum. Implementation with good and correct worship habits becomes a reinforcement in the development of student character. Implementation of the JSIT curriculum, but all of this must be a perception of thinking and acting by providing self-development and training or web wins for HR at SDIT Harum. Discrepancy evaluation is one type of evaluation approach in evaluating a integrated islamic school network curriculum program. The results of this evaluation are to find out the gaps that occur between the expected conditions and the reality in the field, the next step in making decisions.